Beauty and the pathogens: A leaf-less control presents a better image of Cymbidium orchids defense strategy - Ahmad, Sagheer; Chen, Guizhen; Huang, Jie; Yang, Kang; Hao, Yang; Zhou, Yuzhen; Zhao, Kai; Lan, Siren; Liu, Zhongjian; Peng, Donghui (Frontiers in Plant Science, 2022)
Biological control is a safe way of combating plant diseases using the living organisms. For the precise use of microbial biological control agents, the genetic information on the hypersensitive response (HR), and defense-related gene induction pathways of plants are necessary. Orchids are the most prominent stakeholders of floriculture industry, and owing to their long-awaited flowering pattern, disease control is imperative to allow healthy vegetative growth that spans more than two years in most of the orchids. We observed leaf-less flowering in three orchid species (Cymbidium ensifolium, C. goeringii and C. sinense). Using these materials as reference, we performed transcriptome profiling for healthy leaves to identify genes specifically involved in plant-pathogen interaction pathway. There were 253 differentially expressed genes identified in C. ensifolium, 189 in C. goeringii and 119 in C. sinense. Bacterial secretion systems, FLS2, CNGCs and EFR were the key routes with enormous number of DEGs found in three species, mainly regulating HR, stomatal closure and defense-related gene induction. FLS2 (LRR receptor-like serine/threonine kinase) contained the highest number of DEGs among three orchid species, followed by calmodulin. Highly upregulated gene sets were found in C. sinense as compared to other species. The great deal of DEGs related to defense and immunity responses can effectively direct the future of biological control of diseases for orchids.